Ce que les interactions nous disent sur l'activité de l'enseignant et des étudiants pendant le cours par visioconférence en situation de contrainte - Saida Mraihi (Centre National d'Enseignement à Distance, 2024)
This paper focuses on the analysis of teacher and student activity during the videoconference course which has grown considerably during the COVID-19 health crisis, by taking as object of study the interactions that take place between these two actors. The urgent transition to distance learning has forced teachers and students to adapt their activity to new training modalities. The classroom is transported to the private space or to another professional space such as the office and the teacher and students take part in the course in a virtual space through a screen. Our research aims to understand how teachers and students interact in this new environment. In this paper, we present the theoretical framework that guided our research, we outline our mixed research methodology based on qualitative and quantitative data and finally we share specific elements of our result by focusing on the degree of multimodality of interactions in videoconference course and the effects induced by physical and technical environment.